Managers and efficiency in banking - Kauko, Karlo (Journal of Banking & Finance, 2009)
This paper presents evidence on the impact of managers on cost efficiency in banking. Stochastic frontier analysis is applied to a unique Finnish data set. Manager age and education have strong yet complicated effects on efficiency. The impact of age on efficiency depends on education. A university degree is useful mainly in the largest banks of the sample. Educational background seems to be less important for young managers than for mature ones. Managing director changes are systematically followed by efficiency changes. Retirement typically causes an efficiency improvement whereas other manager changes can either improve or weaken efficiency. However, in many cases mature managers outperform their young colleagues.